Singapore : Report on the Observance of Standards and Codes. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses findings of the Report on Observance of Standards and Codes on Singapore. The Monetary Authority of Singapore (MAS) shows a very high level of compliance with the Basel Core Principles and demonstrates a strong commitment by MAS to their implementation. As a large financial center, MAS is well aware of the risks posed by a financial system that is significantly larger than the economy of Singapore, and comprised primarily of branches of foreign institutions operating in non-Singapore dollars. MAS has also set a high standard for approving foreign entrants, applying the same prudential framework to foreign branches as to its own locally incorporated banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet